PENENTUAN NILAI SPF ( SUN PROTECTION FACTOR) EKSTRAK DAN FRAKSI DAUN KECOMBRANG (ETLINGERA ELATIOR) SECARA IN VITRO MENGGUNAKAN METODE SPEKTROFOTOMETRI - Oktariani Pramiastuti (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
Sunlight is needed by all living things to their survival. One of the benefits of sunlight is as sources of energy and making healthy skin and bones. Kecombrang leaf contains phenolic compound which is able to give protection for UV light and have potentially sunscreens. The research aimed to determine of SPF of water extract, n-hexane fraction, and ethyl acetate fraction of kecombrang leaf. The research was in vitro by using spectrophotometry UV-Vis method. The absorbance of extract and fraction of kecombrang leaf was measured at a UV-B light wave length of 290-320 nm. Determination of SPF was based on Mansur equation. Phytochemical test in TLC of water extract, n-hexane fraction, and ethyl acetate fraction was positive for phenol in each. The result showed that water extract of kecombrang leaf had the highest SPF at concentration of 300 ppm numbered 7.30±0.62 with level of extra sunscreens ability; n-hexane fraction of kecombrang leaf had the highest protection activity in a SPF of 17.57±2.49 with level of ultra-sunscreens ability in a concentration of 300 ppm; while ethyl acetate fraction had the highest SPF namely 2.65±0.12 with the minimum protection. The data analysis stated that there was a significant difference between water extract of kecombrang leaf and fractions of n-hexane and ethyl acetate. To sum up, n-hexane fraction of kecombrang leaf had the highest SPF so that it had potentially as sunscreens for UV-B light protectionKeywords: Kecombrang Leaf, SPF, Water Extract, n-hexane fraction, ethyl acetate fraction